2015
DOI: 10.1002/pro.2730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single point mutations in a form of systemic amyloidosis

Abstract: Amyloid deposits of light-chain proteins are associated with the most common form of systemic amyloidosis. We have studied the effects of single point mutations on amyloid formation of these proteins using explicit solvent model molecular dynamics simulations. For this purpose, we compare the stability of the wild-type immunoglobulin light-chain protein REI in its native and amyloid forms with that of four mutants: R61N, G68D, D82I, and A84T. We argue that the experimentally observed differences in the propens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Several mutations on these two sites cause 1REI VL to form either amorphous aggregates or fibrils. Moreover, in silico study suggested that these mutations do not only destabilize the native dimer interface by increasing exposure of certain hydrophobic residues, but also shift the monomers from native structures to amyloid-like structures[56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations on these two sites cause 1REI VL to form either amorphous aggregates or fibrils. Moreover, in silico study suggested that these mutations do not only destabilize the native dimer interface by increasing exposure of certain hydrophobic residues, but also shift the monomers from native structures to amyloid-like structures[56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the structures of amyloidogenic and non‐amyloidogenic proteins are very similar, so we performed molecular dynamics simulations on the germline protein 6aJL2 and two mutants (R24G and P7S) in order to find differences in their dynamic signatures in the native state. While a few molecular dynamic simulations on these domains have been published, they explore mostly kappa Ig light chain variable domains. These studies are centered in the protein REI and point mutants surrounding the E‐F loop, at the opposite end of the CDR1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were research efforts that focused on basic mechanisms such as protein stability and conformational dynamics (Bhavaraju and Hansmann, 2015 ; Getov et al, 2016 ). Many other studies were also reported, including an analysis of full length amylin oligomer aggregation (Berhanu and Masunov, 2014 ), effects of single point mutations on amyloid formation (Bhavaraju and Hansmann, 2015 ; Getov et al, 2016 ; Petukh et al, 2016 ), interactions between methylated histone H3 and effector domains of the PHD family in pursuit of a molecular mechanism of epigenetics (Grauffel et al, 2015 ), the binding mechanism of actin-depolymerizing factor 1 and G-actin (Du et al, 2016 ), the interaction between phosphotyrosine binding domains and peptides for neuronal development, immune responses, tissue homeostasis, and cell growth (Sain et al, 2016 ), the cognate transducer complex srII-htrII for the downstream signaling mechanism of sensory rhodopsin (Sahoo and Fujiwara, 2017 ), the binding of CBP to c-Myb for understanding the exact function of CBP and its interaction with c-Myb (Odoux et al, 2016 ), the catalytic stability of the tetrameric complex of cystathionine gamma-lyase (El-Sayed et al, 2015 ), the study of the mechanism of a molecular chaperone using acid-stress chaperone HdeA and its substrate protein (Zhou et al, 2017 ), and the binding of thiopeptide to a ribosomal subunit in order to understand the structure–activity relationship of thiostrepton derivatives (Wolf et al, 2014 ).…”
Section: Applications Of Mmpbsamentioning
confidence: 99%